New aspects on patients affected by dysferlin deficient muscular dystrophy. Issue 9 (14th June 2009) - Klinge, Lars; Aboumousa, Ahmed; Eagle, Michelle; Hudson, Judith; Sarkozy, Anna; Vita, Gianluca; Charlton, Richard; Roberts, Mark; Straub, Volker; Barresi, Rita; Lochmüller, Hanns; Bushby, Kate
Abstract : Mutations in the dysferlin gene lead to limb girdle muscular dystrophy 2B, Miyoshi myopathy and distal anterior compartment myopathy. A cohort of 36 patients affected by dysferlinopathy is described, in the first UK study of clinical, genetic, pathological and biochemical data. The diagnosis was established by reduction of dysferlin in the muscle biopsy and subsequent mutational analysis of the dysferlin gene. Seventeen mutations were novel; the majority of mutations were small deletions/insertions, and no mutational hotspots were identified. Sixty-one per cent of patients (22 patients) initially presented with limb girdle muscular dystrophy 2B, 31% (11 patients) with a Miyoshi phenotype, one patient with proximodistal mode of onset, one patient with muscle stiffness after exercise and one patient as a symptomatic carrier. A wider range of age of onset was noted than previously reported, with 25% of patients having first symptoms before the age of 13 years. Independent of the initial mode of presentation, in our cohort of patients the gastrocnemius muscle was the most severely affected muscle leading to an inability to stand on tiptoes, and lower limbs were affected more severely than upper limbs. As previous anecdotal evidence on patients affected by dysferlinopathy suggests good muscle prowess before onset of symptoms, we also investigated pre-symptomatic fitness levels of the patients. Fifty-three per cent of the patients were very active and sporty before the onset of symptoms which makes the clinical course of dysferlinopathy unusual within the different forms of muscular dystrophy and provides a challenge to understanding the underlying pathomechanisms in this disease.